Kinetics of the liquid phase selective hydrogenation of 2,3-butanedione over new composite supported Pd catalysts - Carrara, Nicolás Ricardo (2013)
BACKGROUND: Heterogeneous hydrogenation catalysts for fine chemical synthesis are a convenient alternative to homogeneous catalysts because of the ease of separation and reuse. In order to be good catalysts they must have high activity and selectivity and good mechanical properties. Appropriate kinetic models should also be available for reactor design. Novel composite supported Pd catalysts were synthesized and tested in the liquid-phase selective hydrogenation of 2,3-butanedione to 3-hydroxy-2-butanone (acetoin). The composite support comprised a mixture of an organic polymer and γ-Al2O3. The support and the Pd catalyst were further characterized by XRD, SEM, EMPA and XPS spectroscopy. Catalytic tests at various conditions were performed in order to elucidate the kinetics of the system. RESULTS: The composite had better mechanical properties (resistance to radial and axial compression) in comparison with other commercial supports. Good activity and high selectivity to acetoin, a product of partial hydrogenation, were obtained at different reaction conditions. A Langmuir-Hinshelwood chemical rate expression useful for reactor design was regressed from the kinetic data. CONCLUSIONS: The experimental results could be explained by a Horiuti-Polanyi mechanism in which the addition of an H atom to the carbonyl group in the adsorbed state is the rate limiting step.